Obstacles to the use of educational technologies in teaching people with special needs from the point of view of female teachers in the city of Sebha *A field study (Journal of Human Sciences, 2023)
The aim of the current research is to identify the "obstacles to the use of educational technologies for people with special needs from the point of view of female teachers in Sebha" attributable to some variables (type of disability - number of years of educational experience - number of training courses obtained in the field of educational technologies). And then using the questionnaire "Obstacles to educational technologies" prepared by the two researchers, and it includes (23) items distributed on (3) axes, and the research sample included (60) female teachers, and the study reached several results, which are the following: There are obstacles to the use of educational technologies for people with special needs From the point of view of female teachers in Sebha city, it also indicates the arithmetic mean of the questionnaire as a whole and of the axes. As for the study variables, there are no statistically significant differences in Obstacles to the use of educational technologies for people with special needs from the point of view of female teachers in Sebha, due to the variable (type of disability - years of educational experience). As for the variable "the number of training courses obtained in the field of educational technologies": (one-two-3 courses and more), there are statistically significant differences on the questionnaire as a whole, as for the axes, there are no statistically significant differences for the first axis, "obstacles of the master teacher" Using the teaching aids "according to (one-two-3 courses and more). From the point of view of parameters. While there are statistically significant differences on the second and third axis "goals of achieving the educational plan using educational technologies - obstacles for people with special needs using educational technologies". According to the variable number of training courses obtained in the field of educational techniques from the point of view of female teachers in Sebha, and it was in favor of the number of courses (3 courses and more).